2017
DOI: 10.5296/jet.v4i1.10933
|View full text |Cite
|
Sign up to set email alerts
|

Mind the Gap: Exploring Hospitality Teachers’ and Student Interns’ Perception of Using Virtual Communities for Maintaining Connectedness in Internship

Abstract: Considerable attention has been given to the relationship between internship and hospitality education and positive results have been extracted. More and more hospitality programs worldwide emphasize the necessity of internship; nevertheless, intern students always considered the lack of support from academic staff as a major challenges for teachers to overcome and virtual community can be exploited as a venue to provide such assistance. The present study surveyed 230 teachers and 660 intern students of hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
2
0
1
Order By: Relevance
“…Through data analysis, we found that, regarding technological knowledge, university-level and junior high teachers deemed themselves more proficient in technology-based education than did their peers at other levels. Possible explanations are twofold: firstly, teachers at university level have more access to ICT in their research projects, and university students have more latitude to use social media to contact their teachers [82]. Secondly, more training programs are available to in-service teachers at junior high level in Taiwan [83].…”
Section: Discussionmentioning
confidence: 99%
“…Through data analysis, we found that, regarding technological knowledge, university-level and junior high teachers deemed themselves more proficient in technology-based education than did their peers at other levels. Possible explanations are twofold: firstly, teachers at university level have more access to ICT in their research projects, and university students have more latitude to use social media to contact their teachers [82]. Secondly, more training programs are available to in-service teachers at junior high level in Taiwan [83].…”
Section: Discussionmentioning
confidence: 99%
“…Hospitality industry employees and owners strive for effective leaders to interact with customers and employees alike (Butler et al, 2014). These leadership competencies and expectations of the industry still prompt discussions among hospitality educators and research about course curriculum (Hsu, 2017;Hsu et al, 2017;Min et al, 2016). Curriculum discussions should focus on imperative changes to meet industry expectations.…”
Section: Leadership For Industry Imperative Impact On Higher Educationmentioning
confidence: 99%
“…Öğrencilerin psikolojik ve sosyal durumlarını takip etmeli, işletme ile arasındaki ilişkileri düzenlemede yardımcı olmalı ve okul idaresiyle öğrenci ile işletme arasında köprü görevi görmelidir (Sarı, 2007 Bu yeniliklerden birisi internet ve sosyal medya aracılığıyla iletişimin sağlanması, hızlı ve etkili iletişimle kısa zamanda alınan eğitimin verimliliği arttırılabilir. Turizm beceri eğitiminde de öğretmenler öğrencilerle buna benzer teknikler kullanabilirler (Hsu, 2017…”
Section: Beceri Eğitiminde Koordinatör öğRetmenin Konumuunclassified